Using the second equation, let’s find x
x + 7y = 8
x = 8 - 7y
Substitute x in the other equation
3/8(8 - 7y) + 1/3y = 17/24
3 - 21/8y + 1/3y = 17/24
-55/24y = -55/24
y = 1
Plug in y in any equation
x + 7(1) = 8
x + 7 = 8
x = 1
x = 1 and y = 1
Answer:
Step-by-step explanation:
7x - 1 + 6x - 1 = 180
13x - 2 = 180
13x = 182
x = 14
7(14) - 1 = 98 - 1= 97
6(14) - 1 = 84 - 1 = 83
Answer:
2a to the second power + 3a
Step-by-step explanation:
Answer:
8x +3
Step-by-step explanation:
Just collect the like terms, like terms have the same variable. So in this case, 2x, 3x, 3x all share the variable x, so we can add it together.
So when simplified:
2x +3x + 3x+ 3 = 8x +3
Hope this helped,
Cate
Answer: (-4, -2) and (6, -2)'s slope is 0, (2,9) and (2, -5)'s is undefined
Step-by-step explanation:
bro its not that hard, y1-y2 divided by x1-x2